ANALISIS EKONOMI MESIN PERONTOK (POWER THRESHER) KEDELAI TIPE MPT 001 - Putria G. Rompas; Robert Molenaar; David P. Rumambi (COCOS, 2021)
AbstractThis study aims to analyze the economy, total costs and economic feasibilityof the soybean threshing process using the power thresher MPT 001 Type atLolah Satu Village, East Tombariri District, Minahasa Regency. Break evenpoint value or operational break even point of the power thresher MPT 001Type is at an operating level of 17.866,53 kg/year or equivalent to Rp.7.878.577/year. Analysis of the operational feasibility of the power thresherMPT 001 Type based on the amount of service potential available using acommercial scale calculation base is, resuted NPV value of Rp.302.056.654,69, the IRR of 195,982%, the B/C ratio of 1.4497. This conditionshows that the power thresher MPT 001 Type is economically feasible. Basedon the existing condition on site the machine does not fulfil the operationconditions that guarantee sustainability. The sensitivity analysis shows thatchanges in the level of working hours per year and the price of drying servicesare very influential on the feasibility of operations with the lowest level beingthe service price of 1.1 times the total cost of threshing services.Keywords: economics analysis. power thresher, soybean